Psoty i klopoty wrobelka Elemelka - Lochocka, Hanna; Witwicki, Zdzislaw (Warszawa : Nasza Ksiegarnia, 1994)
A story about a sparrow, for children. Ages 6-10.
Keywords: Sparrows -- Juvenile fiction; Children's stories, Polish